Exploring genetic variability in bael - SINGH, A K; Singh, Sanjay; Saroj, P L; Mishra, D S; Yadav, Vikas (Indian Horticulture, 2019)
Bael is a culiflorous and ramiflorus tree which is common in Goma Yashi and NB-16. Vivipary which was also observed in genotype CHESB-29 is of unusual occurrence in bael. High humidity and warm weather appears to be associated with the viviparous fruits in bael. The pollen of bael has been found to exert a direct influence on the size, shape and styler end cavity of fruit, and the speed of development of the fruit and on the time of ripening of the fruit of the asexually propagated bael plant. Such influence on fruit may be due to metaxenia effect in bael. Variations in number of petals and sepals, number of leaflets and thorns were also observed in different bael germplasm.